Quinone Methides: Photochemical Generation and its Application in Biomedicine - Basaric, Nikola; Mlinaric-Majerski, Kata; Kralj, Marijeta (Current Organic Chemistry, 2014)
Quinone methides (QMs) are important intermediates in chemistry and biochemistry of phenols that are characterized by wide biological activity. Some classes of anticancer antibiotics exhibit their effect due to methabolic formation of QMs that alkylate DNA. Photochemical reactions provide mild and easy approach to QMs. Photoreactions that give QMs include cleavage of oxa-heterocycles, dehydrohalogenation, dehydration, deammination, excited state intramolecular proton transfer (ESIPT) and tautomerizations of phenols. This critical review (137 references) features different photochemical reactions giving QMs that are applicable in biology and medicine.
Keywords: quinone methides